ВИХОВНА СИСТЕМА ШКОЛИ: СУТНІСТЬ ТА СТРУКТУРА - Гагарін, Микола (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті описуються різноманітні підходи до визначення загальнонаукового поняття «система», висвітлено сутність поняття «виховна система», «виховна система школи», проаналізовано різні погляди науковців щодо визначення її структури та особливостей. Метою статті є розкриття сутності та структури виховної системи школи. У статті акцентується увага на розгляді функцій виховної системи, компонентів та взаємозв’язку між ними. Доводиться важливість такого підходу як системний підхід у вихованні. Робиться висновок, що феномен виховної системи школи є складним та багатомірним явищем, а створення в кожному навчальному закладі власної виховної системи є одним з надважливих та актуальних завдань на сучасному етапі розвитку освіти. В статье описано различные подходы до определения общенаучного понятия «система», освещено сущность понятия «воспитательная система», «воспитательная система школы», проанализировано разные взгляды ученых относительно ее структуры и особенностей. Целью статьи есть раскрытие сущности и структуры воспитательной системы школы. В статье акцентируется внимание на рассмотрении функций воспитательной системы, компонентов и взаимосвязи между ними. Доказывается важность такого подхода как системный подход в воспитании. Делается вывод, что феномен воспитательной системы школы является сложным и многомерным явлением, а создание в каждом учебном заведении собственной воспитательной системы есть одним из сверхважных и актуальных задач на современном этапе развития образования. The article presents various approaches to the definition of the scientific term «system», highlights the essence of the concept «educational system», «school educational system», analyzes different scholarly perspectives of determination of its structure and peculiarities. The aim of the article is to reveal the essentials and the structure of the educational system of the school. The article focuses on investigation of the functions of the educational system (integrating, regulating, developing, protective, corrective, compensatory, rehabilitative), which provide its effective influence on the personality, as well as components (educational aim, goals, objectives, subjects, activities and communication, relations, interaction, living space), and the relations between them. The importance of psychological, educational and social factors that determine the specificity and peculiarity of the formation of the school educational system is emphasized. The potential and features of the use of the educational school system to ensure optimal development of the educational establishment are considered. The importance of the system approach in education is proved. It is concluded that the phenomenon of the school educational system is complex and multivariate, and the establishment of each educational institution’s peculiar educational system is one of the most important and urgent tasks at the current stage of the development of education.